2022
DOI: 10.53730/ijhs.v6ns4.11954
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of fimH& mrkDgenes of strong biofilm producers & MDR Klebsiella pneumoniae

Abstract: Klebsiella pneumoniae is an adaptable pathogen that forms biofilms on a variety of surfaces. This study's objective was to identify the presence of fimbrial genes (types 1 and 3) in K. pneumoniae strains isolated from various clinical sources based on their antibiotic resistance and ability to form biofilms. According to identification utilizing the vitek 2 technology and confirmation by molecular identification targeting the 16S rRNA gene with a particular primer, forty isolates were identified from clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These results agreed with a local study in Baghdad city done by Ali et al, 15 in which it was observed that out of 39 K. pneumoniae isolates, 1 (2.56%) was a moderate biofilm producer, 21 (53.85%) were weak biofilm producers, and 17 (43.59%) were non-producers. On the contrary, a local study by Jabar et al 16 found that all K. pneumoniae isolates were strong biofilm producers, apart from their origin. Also, the present findings were in disagreement with the study by Makhrmash et al 3 as they revealed that among 56 isolates of K. pneumoniae, 10 (18%) formed weak biofilm, 14 (25%) formed moderate biofilm, and 32 (57%) formed strong biofilm.…”
Section: Discussionmentioning
confidence: 87%
“…These results agreed with a local study in Baghdad city done by Ali et al, 15 in which it was observed that out of 39 K. pneumoniae isolates, 1 (2.56%) was a moderate biofilm producer, 21 (53.85%) were weak biofilm producers, and 17 (43.59%) were non-producers. On the contrary, a local study by Jabar et al 16 found that all K. pneumoniae isolates were strong biofilm producers, apart from their origin. Also, the present findings were in disagreement with the study by Makhrmash et al 3 as they revealed that among 56 isolates of K. pneumoniae, 10 (18%) formed weak biofilm, 14 (25%) formed moderate biofilm, and 32 (57%) formed strong biofilm.…”
Section: Discussionmentioning
confidence: 87%